Beyond Religiosity: How Social Capital Drives Institutional Zakat Payment Preferences in Indonesia - A Behavioural Economics Analysis - Djayusman, Royyan Ramdhani; Ibnu, Adi Rahmannur; Lahuri, Setiawan bin; Jalili, Ismail (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
Notwithstanding the fact that Indonesia has the world’s largest Muslim population, zakat collection through formal institutions is substantially below expectations. In light of this shortfall, this study investigates the interplay between religiosity and social capital on individual preferences for zakat payments and the proportion allocated to official zakat agencies, with the overarching aim of contextualizing the fiqh zakat framework in contemporary Indonesia. Drawing upon the data from a nationwide survey of 794 respondents, the empirical analysis employs Linear Probability Model (LPM) and Poisson Pseudo Maximum Likelihood (PPML) regression techniques to examine the determinants of zakat payment behaviour. Findings reveal that social capital significantly increases both the likelihood of choosing zakat institutions and the portion of zakat paid through them. In contrast, religiosity shows a weaker direct effect on institutional zakat payment. Taken together, these results highlight the pivotal role of social networks and trust in enhancing institutional zakat collection. Therefore, the study advocates for a strategic reform of fiqh zakat practices that integrate social capital strategies to reinforce religiosity and improve zakat compliance through formal channels.